2021
DOI: 10.5219/1693
|View full text |Cite
|
Sign up to set email alerts
|

Antibiofilm and antioxidant activity of Rosmarinus officinalis essential oil

Abstract: The aim of the work was to explore the antioxidant potential and antibiofilm activity of the Rosmarinus officinalis essential oil. The DPPH method was used to determine the antioxidant activity. The agar microdilution method was used to determine the minimum biofilm inhibiting concentration (MBIC). The MALDI-TOF MS Biotyper was used to evaluate the antibiofilm activity on the wood and glass surface. Vapor phase antimicrobial analysis was used to determine the effect on the food model. The antioxidant activity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Antioxidant activity and acetylcholinesterase inhibition; Antiproliferative activities [29][30][31][32][33][34][35] Thymus mastichina Antioxidant potential and Acetylcholinesterase inhibition, Lipoxygenase inhibition and anti-tumoral activities [26,27,36] officinallis with high content of 1,8-cineole reported that it could inhibit lipid peroxidation and capture free radicals [29,31,32,34]. Studies carried out with T. mastichina EOs from Spain and Portugal showed that their EOs have shown low antioxidant activity by the DPPH radical method [26,36,119].…”
Section: Rosmarinus Oficinallismentioning
confidence: 99%
See 1 more Smart Citation
“…Antioxidant activity and acetylcholinesterase inhibition; Antiproliferative activities [29][30][31][32][33][34][35] Thymus mastichina Antioxidant potential and Acetylcholinesterase inhibition, Lipoxygenase inhibition and anti-tumoral activities [26,27,36] officinallis with high content of 1,8-cineole reported that it could inhibit lipid peroxidation and capture free radicals [29,31,32,34]. Studies carried out with T. mastichina EOs from Spain and Portugal showed that their EOs have shown low antioxidant activity by the DPPH radical method [26,36,119].…”
Section: Rosmarinus Oficinallismentioning
confidence: 99%
“…Most of them belong to the Lamiaceae family and include Lavandula spp., Calamintha spp., Rosmarinus spp. and Thymus spp., in which EOs show chemical polymorphism with high content in 1,8-cineole and that are recognized for their antioxidant and anti-inflammatory potential [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36].…”
Section: Introductionmentioning
confidence: 99%